Perbedaan Rata-Rata Kadar Hb dengan Penggunaan Modul Tata Laksana Home Visit dan Konsumsi Daun Kelor pada Ibu Menyusui Anemia di Karawang - Ari Antini; Irna Trisnawati (FORIKES, 2021)
Anemia in pregnancy will increase the incidence of anemia in postpartum mothers by 20-30%. The prevalence of anemia in postpartum women in 2012 was 45.1%. The most common causes of postpartum anemia are insufficient iron requirements during pregnancy and complications of childbirth. Moringa oleifera leaves are proven to have higher Fe content compared to other green vegetables, which is 28.29 mg so that they can be used as an alternative to treat anemia. A preliminary study at the research location found an incidence of anemia as much as 40%. The purpose of this study was to know the difference in the average Hb level with the use of the home visit management module and the provision of Moringa leaves to anemic breastfeeding mothers. The design of this study was a quasiexperimental study, with the intervention group being anemic postpartum mothers who were given modules and consuming Moringa leaves, the non-intervention group being anemic postpartum mothers who were given modules. The population in this study were all anemia breastfeeding mothers in Karawang. The sample in this study were some anemia breastfeeding mothers who had inclusion criteria. A sample of 30 respondents both in the intervention group and the non-intervention group. The average Hb level of breastfeeding mothers who were given Moringa leaves and modules was 12.433 g% with a standard deviation of 0.8938 g%. Meanwhile, the Hb level in the module group was 11.533 g% with a standard deviation of 0.149 g%. The results of the statistical test showed that the value of p = 0.000, meaning that there was a significant difference in the average Hb levels in the Moringa leaf and module groups compared to the module alone. This shows that the provision of Moringa leaves and moduls proved to be effective in increasing the hemoglobin levels of anemic breastfeeding mothers.Keywords: moringa leaves; postpartum; anemiaABSTRAKAnemia pada kehamilan akan meningkatkan kejadian anemia pada ibu nifas sebanyak 20-30%. Prevalensi anemia pada ibu nifas tahun 2012 sebesar 45,1%. Penyebab paling umum dari anemia masa nifas adalah kebutuhan Fe yang tidak tercukupi saat hamil dan komplikasi persalinan. Daun kelor (Moringa oleifera) terbukti memiliki kandungan Fe yang lebih tinggi dibanding dengan sayuran hijau lainnya yaitu sebesar 28,29 mg sehingga dapat dijadikan alternative untuk penanganan anemia. Studi pendahuluan dilokasi penelitian ditemukan kejadian anemia sebanyak 40% Tujuan penelitian ini adalah Diketahui perbedaan rata-rata kadar Hb dengan penggunaan modul tatalaksana home visit dan pemberian daun kelor pada ibu menyusui anemia. Desain penelitian ini adalah quasi eksperimen, dengan kelompok intervensi adalah ibu nifas anemi diberi modul dan konsumsi daun kelor, kelompok non intervensi adalah ibu nifas anemi dengan diberi modul. Populasi pada penelitian ini adalah seluruh ibu menyusui anemia di Karawang. Adapun Sampel pada penelitian ini adalah sebagian ibu menyusui anemia yang memiliki kriteria inklusi. Sampel sebesar 30 responden baik pada kelompok intervensi maupun kelompok non intervensi. Rata-rata kadar Hb ibu menyusui yang diberikan daun kelor dan modul adalah 12,433 g% dengan standar deviasi 0,8938 g%. Sedangkan untuk kadar Hb kelompok modul adalah 11,533 g% dengan standar deviasi 0,149 g%. Hasil uji statistik didapatkan nilai p = 0,000, berarti terlihat ada perbedaan yang signifikan rata-rata kadar Hb pada kelompok pemberian daun kelor dan modul dibanding pemberian modul saja. Hal ini menunjukan bahwa pemberian daun kelor dan modul terbukti efektif terhadap peningkatan kadar Hb ibu menyusui anemia.Kata kunci: daun kelor; nifas; anemi